Optimized Variables for Environmental Dynamics: China’s Renewable Energy Policy - Wang, Yujing; You, Yanqun; Teng, Yu (Frontiers in Environmental Science, 2022)
The study purpose is determine the impacts of foreign direct investment (FDI), renewal energy (RE), energy consumption index (ECI), Globalization (GLO) and green technology innovation (GTI) on environmental pollution using a time series data from 1980 to 2019, using DARDL assessor looked at how markers with high levels of petroleum derivatives distorted the explanatory variable in China. The results showed that GTI contaminated ES. The polluted safe house notion claimed that FDI has a negative impact on the country's inherent character. Finally, an ES is waking up and taking notice of the state of affairs. Single-headed causalities from GTI to carbon emissions were detected in the middle of the other causes and fossil fuel byproducts need to change into green energy resources to reduce the environmental pollution. Finally the research proved that the FDI is a major source of environmental pollution in China. According to the findings of the DARDL research, foreign direct investment and urbanization, green technological innovations, and China's environmental pollution policy direction are all congruent with each other.